The strength of sensitivity to ambiguity - Robin Cubitt; Gijs van de Kuilen; Sujoy Mukerji (Queen Mary University of London, School of Economics and Finance, 2017)
We report an experiment where each subject's ambiguity sensitivity is measured by an ambiguity premium, a concept analogous to and comparable with a risk premium. In our design, some tasks feature known objective risks and others uncertainty about which subjects have imperfect, heterogeneous, information (''ambiguous tasks''). We show how the smooth ambiguity model can be used to calculate ambiguity premia. A distinctive feature of our approach is estimation of each subject's subjective beliefs about the uncertainty in ambiguous tasks. We find considerable heterogeneity among subjects in beliefs and ambiguity premia; and that, on average, ambiguity sensitivity is about as strong as risk sensitivity.
Keywords: C91; D01; D03; D80; G02; 330; Ambiguity sensitivity; ambiguity attitude; measuring strength of ambiguity sensitivity; smooth ambiguity model; ambiguity premium